Grandes grupos no Brasil: Estratégias e desempenho nos anos 2000 - Célio Hiratuka; Marco Antonio Martins da Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Though a fairly common phenomenon both in developed and in developing countries, the economic groups are still organizations that have received little attention. Only more recently the economic literature and other social sciences have studied the issue more systematically. This paper aims to contribute to the understanding of the role of large national groups in the Brazilian economy in recent years. Based on the analysis of the performance of the 200 largest Brazilian groups and a more detailed monitoring of a panel of 25 relevant groups, the paper seek to interpret their major strategic movements in terms of diversification, forms of entry into new areas of business and internationalization. The paper is divided into four sections, besides the introduction and concluding remarks. Section 2 provides a brief review of the international literature on economic groups, calling attention to an alternative vision hardly present in international studies. Section 3 presents a retrospective of the development of Brazilian economic groups and emphasizes the major changes in the macroeconomic environment that conditioned the strategies of these groups in the 2000s. Section 4 analyzes the performance of the 200 largest Brazilian groups and presents an overview of the strategies of 25 national groups selected from the top 200. Finally, the concluding remarks emphasize the main results found throughout the work.
Keywords: D22; N86; L10; 330; business group; diversification; Brazilian economic groups